2021
DOI: 10.1111/jav.02597
|View full text |Cite
|
Sign up to set email alerts
|

Diel at‐sea activity of two species of great albatrosses: the ontogeny of foraging and movement behaviour

Abstract: The first year of life is a period of high mortality in animals. Reduced foraging capacities of naive individuals might be the primary cause of their mortality. These capacities are supposed to be progressively acquired during the first months of life. In this study, we investigate the ontogeny of flight capacities, by day and night, of first‐year individuals, and compare it with adults from two closely related species of great albatrosses: Amsterdam Diomedea amsterdamensis and wandering Diomedea exulans albat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…The lower performance of juveniles we found is consistent with studies on wandering albatrosses and Amsterdam albatrosses (Riotte-Lambert and Weimerskirch 2013; de Grissac et al 2017;Pajot et al 2021) during the first weeks at sea, which found that shortly after fledging juvenile albatrosses employ similar foraging strategies as adults. Additional skills need to be acquired during the immature period before the efficiency of these behaviors matches that of adults.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The lower performance of juveniles we found is consistent with studies on wandering albatrosses and Amsterdam albatrosses (Riotte-Lambert and Weimerskirch 2013; de Grissac et al 2017;Pajot et al 2021) during the first weeks at sea, which found that shortly after fledging juvenile albatrosses employ similar foraging strategies as adults. Additional skills need to be acquired during the immature period before the efficiency of these behaviors matches that of adults.…”
Section: Discussionsupporting
confidence: 90%
“…Though the diet and foraging strategy of Amsterdam albatross remains poorly known, it is presumed to have very similar foraging behaviour compared to that of the Wandering albatross, although subtle differences can appear (Pajot et al 2021). Although Amsterdam albatross is 5-8% smaller and 25% lighter than wandering albatross, the two species have a very close anatomy and similar use of the wind.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual steps were then assigned to daylight or darkness using function crepuscule in package maptools to determine the timing of civil twilight, when the sun is 6 degrees below the horizon (Bivand and Lewis‐Koh 2017). Step lengths of birds were much shorter during darkness than daylight (9.1 ± 12.1 versus 23.7 ± 18.1 km h −1 ) suggesting that juveniles rarely travel or search for prey during darkness (Supporting information and in line with de Grissac et al 2017, Pajot et al 2021); hence steps occurring during the night were excluded from the i SSA. A further two birds were removed from the final test dataset as observations were too few (< 26) to account for within‐individual temporal autocorrelation.…”
Section: Methodsmentioning
confidence: 82%